Integrating GitMind into Socio-Scientific Inquiry-Based Learning: Impacts on Science Literacy and Argumentation Skills - Afifah Zahrah Pamela; Susriyati Mahanal; Sitoresmi Prabaningtyas (Madrasah Tsanawiyah DDI Cilellang, 2026)
Science literacy and argumentation skills are two essential competencies for addressing socio-scientific issues, yet both remain relatively low among high school students in Indonesia. No prior study has integrated digital mind-mapping tools within a Socio-Scientific Inquiry-Based Learning (SSIBL) framework to simultaneously develop these competencies, constituting the primary novelty of this work. This quasi-experimental study compared three instructional conditions: GitMind-assisted SSIBL, Guided Inquiry, and Direct Instruction. Participants were senior high school biology students studying the human reproductive and excretory systems, and ANCOVA was applied to control for pre-existing ability differences. The GitMind-assisted SSIBL class achieved the highest enhancement in science literacy (66.22%), outperforming Guided Inquiry (53.17%) and Direct Instruction (44.87%). Argumentation skills followed the same pattern, with SSIBL recording the greatest improvement (58.47%), followed by Guided Inquiry (46.09%) and Direct Instruction (34.35%). ANCOVA confirmed significant effects of instructional treatment on science literacy, F(2, 89) = 63.615, p < .001, partial η² = .588, and on argumentation skills, F(2, 89) = 82.253, p < .001, partial η² = .649. These findings provide theoretical support for the role of socioscientific context and digital knowledge externalisation in fostering higher-order competencies, and offer biology educators a structured, evidence-based instructional model applicable beyond conventional inquiry approaches.